Assessing persistence of the American pika at historic localities in California's Northern Sierra Nevada - Joseph A. E. Stewart; David H. Wright (Wildlife Society Bulletin)
Abstract The American pika (Ochotona princeps) appears to have experienced a substantial upslope range contraction in the Great Basin in response to climate warming. In California, models predict range contraction, but whether the species' lower elevational limit has already shifted remains unclear. We located and determined current occupancy at 19 historic pika localities in the northern Sierra Nevada of California, USA, in 2009–2012. We found that 17 localities were currently occupied by pikas at or near the original record location, while at 2 localities pikas appeared extirpated. No strong climate signal was detected in our data; however, the distribution of historic points does not allow us to rule out upslope range contraction in our region. Talus area was closely correlated with pika persistence, consistent with the application of metapopulation theory to pikas. © 2012 The Wildlife Society.